2013
DOI: 10.1002/chir.22144
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Asymmetric Styrene Cyclopropanation with a Rhodium(II) Metallopeptide Catalyst Developed with a High‐Throughput Screen

Abstract: Dirhodium metallopeptides have been developed as selective catalysts for asymmetric cyclopropanation reactions. A selective ligand sequence has been identified by screening on-bead metallopeptide libraries in a 96-well plate format. Efficient ligand synthesis and screening allows a 200-member library to be created and assayed in less than three weeks. These metallopeptides catalyze efficient cyclopropanation of aryldiazoacetates, providing asymmetric access to cyclopropane products in high diastereoselectivity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…We previously put into practice these ideas: a screen of several resin types and loadings found that so long as loading is kept low ($0.2 mmol g À1 ), catalytic behavior on resins closely mirrored that in solution. 15,17 We designed and synthesized libraries to assess these ideas using a parallel synthesis approach in a 96-well-plate format previously developed in our group. 15 Starting with 9-mer peptide ligands with rhodium-binding residues at the 3 rd and 7 th residues, we chose for variation specic residues, based on modeling or the results of previous libraries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously put into practice these ideas: a screen of several resin types and loadings found that so long as loading is kept low ($0.2 mmol g À1 ), catalytic behavior on resins closely mirrored that in solution. 15,17 We designed and synthesized libraries to assess these ideas using a parallel synthesis approach in a 96-well-plate format previously developed in our group. 15 Starting with 9-mer peptide ligands with rhodium-binding residues at the 3 rd and 7 th residues, we chose for variation specic residues, based on modeling or the results of previous libraries.…”
Section: Resultsmentioning
confidence: 99%
“…As part of a program aimed at mimicking the properties of metalloenzymes [6][7][8][9][10] for developing asymmetric transition metal catalysts, [11][12][13] and for rhodium(II) carboxylate complexes in particular, we have demonstrated that peptides with two carboxylate side chains (glutamate or aspartate) serve as chelating ligands 12 for rhodium(II), allowing asymmetric catalytic reactions of diazo compounds. [14][15][16][17] Polypeptides are readily optimizable ligands for stereoselective catalysis owing to the chirality and structural variation present in amino acids. [18][19][20] Our initial efforts 14 developed screening methods that identied bispeptide complexes of the type Rh 2 (peptide) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium(II) trifluoroacetate complexes undergo ligand exchange with carboxylate side chains of peptides [132,[166][167][168] in ap rocess that is essentially irreversible under physiological conditions (Figure 27 a). [147,169] Thep roduct metallopeptides are useful for selective catalysis,b oth for asymmetric transformations of small molecules [147,[170][171][172] and for rhodiumcatalyzed, proximity-driven bioconjugation (Section 6.1). In some ways,t hese rhodium-aspartate or -glutamate linkages represent the full scope of the unique capabilities of transition-metal bioconjugation.…”
Section: Rhodium(ii) Carboxylate Complexation:asp Glumentioning
confidence: 99%
“…Rhodium(II)-Trifluoroacetatkomplexeg ehen in einem Prozess,d er unter physiologischen Bedingungen praktisch irreversibel veräuft, mit Carboxylatseitenketten von Peptiden [132,[166][167][168] Ligandenaustauschreaktionen ein (Abbildung 27 a). [147,169] Die als Produkt resultierenden Metallopeptide sind fürd ie selektive Katalyse sowohl in Form asymmetrischer Tr ansformationen kleiner Moleküle [147,[170][171][172] als auch fürd ie rhodiumkatalysierte,p roximitätsvermittelte Biokonjugation (Abschnitt 6.1) nutzbar.I nm ancherlei Hinsicht bilden diese Verbindungen zwischen Rhodium und Aspartat oder Glutamat das einzigartige Potenzial von Übergangsmetallen in der Biokonjugation vollumfänglich ab. Neben ihren katalytischen Eigenschaften bergen sie folgende Vorteile:1)Die Rhodium-Bindung kann eine Kontrolle über die Polypeptidfaltung ermçglichen [173,174] oder als Dreh-und Angelpunkt zur Bildung dimerer oder tetramerer Polypeptidzusammenschlüsse mit interessanten topologischen Auswirkungen dienen.…”
Section: Rhodium(ii)-carboxylatkomplexierung:asp Gluunclassified